Analyzing the effect of employee cultural diversity on organizational performance – a case study of electoral commission –Ghana. - Amoah, Comfort (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirement For The Award At The Master Of Philosophy Degree In Political Science.